Business Continuity in the COVID-19 Emergency: A Framework of Actions Undertaken by World-Leading Companies - Margherita Alessandro; Heikkilä Marikka (Elsevier, 2022)
The COVID-19 emergency has urged companies to operate in new ways to face supply chain interruptions, shifts in customer demand, and risks to workforce health. The organizational ability to respond to critical contingencies is crucial for business leaders in the perspective of continuing business. In our research, we investigate the actions undertaken by 50 world-leading corporations to respond to the pandemic outbreak. Applying content analysis to web pages and social network posts, we extract 77 actions related to 13 sub-areas and integrate these into a five-level framework encompassing operations, customer, workforce, leadership, and community-related responses. We also describe six illustrative company examples of how the emergency can generate opportunities for creating new value. The study advances the scholarly discussion on the impact of emergencies on business continuity and provides managers with a comprehensive view and some insights to define response strategies and actions in the current challenging scenario.